2021
DOI: 10.7759/cureus.20348
|View full text |Cite
|
Sign up to set email alerts
|

A Complicated Case of COVID-19-Induced Inferolateral Wall Myocardial Infarction Successfully Treated With Streptokinase

Abstract: The treatment of myocardial infarction (MI) in coronavirus disease 2019 (COVID-19)-positive patients is both controversial and challenging, particularly in a healthcare setup unable to fulfill COVID-19 protocols. In this report, we describe a case of a COVID-19-positive patient admitted with COVID-19 pneumonia treated symptomatically with a non-rebreathing mask, dexamethasone, remdesivir, and low-molecularweight heparin (LMWH). On day two of the hospital stay, the patient developed inferolateral wall myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…A different study has reported a Covid-19 case with inferolateral ST-elevation MI while the patient was infected with Covid-19 (similar to our case) but with pulmonary involvement and a decreased O2 saturation (unlike our case) [5]. Generally, thrombolytic therapy and conservative treatment are the priority choices for Covid-19 positive patients with ST-elevation MI and NonST-elevation MI, respectively.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…A different study has reported a Covid-19 case with inferolateral ST-elevation MI while the patient was infected with Covid-19 (similar to our case) but with pulmonary involvement and a decreased O2 saturation (unlike our case) [5]. Generally, thrombolytic therapy and conservative treatment are the priority choices for Covid-19 positive patients with ST-elevation MI and NonST-elevation MI, respectively.…”
Section: Discussionsupporting
confidence: 65%
“…Hence, we choose conservative treatment for our patient. Unlike the study [5], no Streptokinase or any other thrombolytic medication were prescribed for our patient due to recovering chest pain and improving evolving MI. Also, no coronary angiography has been performed for the patient in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some cases about COVID-19 patients with AMI have been reported in the literature. 1 2 3 This is the first case of a COVID-19 confirmed patient with AMI in our tertiary center. Despite the time-sensitive nature of AMI, a treatment delay between diagnosis and procedure may occur among COVID-19 patients.…”
mentioning
confidence: 77%